The Black dollar in nineteenth-century Baltimore - Marcus Anthony Allen (Essays in Economic & Business History (EEBH), 2023)
When did Black communities begin having access to significant amounts of money? Were the Black economic enclaves or Black Wall Streets which developed in the first decades of the twentieth century in places like Richmond, Chicago and Durham, the first communities where the Black dollar demonstrated Black economic success? This paper argues that although Blacks in nineteenth-century Baltimore did not demonstrate wealth through widespread property ownership there was a significant amount of money flowing through the Black community. This suggests, apart from its need to solve community problems created by overpopulation and racial discrimination, Baltimore may have been the first noteworthy Black economic enclave in the nineteenth century.
Keywords: 330; African Americans; bank accounts; benevolent organizations; personal wills